Performance Evaluation of Polyethersulfone Membranes for Competitive Removal of Cd2+, Co2+, and Pb2+ Ions from Simulated Groundwater - Salwa H. Ahmed; Sama M. Al-Jubouri; Nasser Zouli; Ahmed A. Mohammed; Hasan Shaker Majdi; Issam K. Salih; Muayad Al-shaeli; Ayham. M. I. Al-Rahawi; Qusay F. Alsalhy; Alberto Figoli (Geofluids)
This paper presents studying the performance of three types of polyethersulfone (PES) membrane for the simultaneous removal of Co2+ ions, Cd2+ ions, and Pb2+ ions from binary and ternary aqueous solutions. Co2+ ions, Cd2+ ions, and Pb2+ ions with two different initial concentrations (e.g., 10 and 50 ppm) were selected as examples of heavy metals that contaminate the groundwater as a result of geological and human activities. This study investigated the effect of types of PES membrane and metal ions concentration on the separation process. For the binary aqueous solutions, the permeation flux of the PES2 membranes was higher for the separation process of solutions containing 50 ppm of Cd2+ ions and 10 ppm of Co2+ ions (24.7 L/m2·h) and Pb2+ ions (23.7 L/m2·h). All the metals in the binary solutions had high rejection when their initial concentration was lower than the initial concentration of the other metal present in the same solution. Using PES2, the maximum rejection of Cd2+ ions was 61.3% when the initial concentrations were 50 ppm Pb2+ ions: 10 ppm Cd2+ ions and 55.4% for Pb2+ ions when the initial concentrations were 10 ppm Pb2+ ions: 50 ppm Cd2+ ions. For the ternary aqueous solutions, the rejection and the permeation flux of the PES membranes increased with decreasing the heavy metal initial concentration. Using PES2, the maximum permeation flux was 21.6 L/m2·h when the initial concentration of the metals was 10 ppm; and the maximum rejection of the metals obtained at initial concentration of 10 ppm was 50.5% for Co2+ ions, 48.3% for Cd2+ ions, and 40% for Pb2+ ions. The results of the filtration process using PES2 of simulated contaminated-groundwater indicated the efficient treatment of groundwater containing Co2+, Cd2+, and Pb2+ ions.